Tách các phân đoạn chitosan chiếu xạ bằng màng siêu lọc và khả năng ứng dụng chúng trong hoàn tất vải bông - Tho, Lưu Thị; Thông, Nguyễn Văn; Hồng Khanh, Vũ Thị; Quỳnh, Trần Minh (Vietnam Journal of Chemistry, 2014)
Three kind of Vietnamese chitosans with the same deacetylation degrees of about 75% and viscosity average molecular weights are 69.000, 187.000 and 345.000Da, respectively, were produced from shrimp shells and cuttle-bone at the MTV chitosan company (Kien Giang). These chitosans were irradiated at 25, 50, 75, 100, 200 and 500 kGy under Cobalt-60 gamma sourse at Hanoi Irradiation Center in order to prepare a series of chitosan segments with wide distribution of molecular weights. Different chitosan samples of the predetermined average molecular weight from 3,000 to 50.000Da were separated from the irradiated chitosans by ultrafiltration with series of filter membranes (Centriprep devices). Moleculer properties of the fragmented chitosans were analysed with gel permeation chromatography, Fourrier transfer infra red spectrometry, and the results suggested that principal characteristics of chitosan were not affacted by gamma irradiation, even its deacetylation degrees was increased. Solubility of the fragmented chitosans were much improved by radiation processing, and the chitosans having molecular weights below 5.000Da were water-soluble polymers, which can easily apply as the auxiliary agent in textile. Keywords: Fragmentation, chitosan, molecular weight, deacetylation degrees, gamma irradiation